Simulation of solid-fuel hybrid combustion - Senchukh, Mykhajlo; Barkovskiy, Arthur (КНУБА, 2017)
There was suggested a numerical model of fuel combustion in the mechanical stocker by applying hybrid process flow. Analytic equations were described for critical parameters calculation of the stack combustion zone and the grate.
Моделювання спалювання твердого палива за комбінованою схемою
Keywords: solid-fuel hybrid combustion; burning rate; numerical model; stack; grate; mechanical stocker; 662.71/.74; 662.93